Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1007/s00484-006-0076-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cold-related complaints, symptoms and injuries in the general population: the FINRISK 2002 cold substudy

Abstract: The prevalence of cold-related complaints and symptoms in the general population has remained unknown. As part of the nationwide FINRISK 2002 health survey performed in Finland, 8,723 people aged 25-64 years filled in a questionnaire asking about the number of hours spent weekly in cold air, their sensations during cold exposure, cold-related complaints, symptoms of diseases, and degradation of performance. Cold thermal sensations at +5 degrees C to -5 degrees C were reported by 35% of men and 46% of women. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
94
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(104 citation statements)
references
References 17 publications
9
94
1
Order By: Relevance
“…This is in line with a report stating that for 22% of the general Finnish population concentration is affected by cold weather (12). A reduced concentration capacity can increase the risk of injuries when operating equipment inside the cold stores.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This is in line with a report stating that for 22% of the general Finnish population concentration is affected by cold weather (12). A reduced concentration capacity can increase the risk of injuries when operating equipment inside the cold stores.…”
Section: Discussionsupporting
confidence: 90%
“…Our results were also higher when compared with a general population exposed to cold during the long winter period. In this population study, the ageadjusted prevalence for peripheral circulatory symptoms was 12% (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(28. ) Besides all its opportunities, the cold environment in northern Finland and exposure to its cold temperatures did cause various coldrelated complaints, symptoms and injuries (8). Nonetheless, most parents estimated that they dealt with their child's outdoor activity very well (20), and confirmed that they added layers to the child's clothing in colder conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to cold temperatures can cause cold-related complaints, symptoms and injuries (8). The type and intensity of cold exposure as well as many individual factors such as age, gender, the layer of insulating fat, previous adaptation and medication interact with cold-related symptoms (9).…”
Section: Introductionmentioning
confidence: 99%